The Use of Zoom Meeting for Distance Learning in Teaching English to Nursing Students during Covid-19 Pandemic - Roudlotun Nurul Laili; Muhammad Nashir (UICELL, 2020)
One of the impacts of Covid-19 pandemic is on educational sector in which the government closes the school access temporarily to avoid the spread of Covid19 and suggests the distance learning by opening educational platform that can be used by the institutions and educators to reach students remotely and limit educational distractions. Zoom cloud meeting is one of the platforms that is widely used as a learning media because this application allows learning activities or discussions like in face to face learning and support communication needs with many people anywhere and anytime without meeting physically. This research intended to describe the conditions occur in distance learning process using zoom as an alternative solving problems and its effectiveness in teaching English to nursing students during covid-19 pandemic. This research method is descriptive qualitative with data collection techniques performed by distributing questionnaire via Google Form and doing interview through Whatsapp video call. The result showed only 44% students mentioned if using zoom is effective in learning English. It indicated that the use of Zoom Meeting is not quite effective because it is constrained by bad network that causes intermittent voice, and the lack of students' level of understanding on the material being taught because English is different from other courses which use our native Indonesian language. Besides, it is difficult in practicing conversations which are carried out in pairs or in groups. However, Zoom application is better than other educational platforms because it facilitates distance learning and enables discussion like in a real classroom.